Variations in rock support capacity due to local variations in bond strength and shotcrete thickness. (October 2021) - Sjölander, Andreas; Ansell, Anders; Malm, Richard
Highlights: Highlighting the correlation between load capacity and shotcrete thickness. Modelling of local variations in shotcrete thickness and bond strength. Verification of material models for interface failure between shotcrete and rock. Local weak zones do not have a significant impact on load capacity. Abstract: Fibre reinforced shotcrete (sprayed concrete) is often used to support tunnels in hard rock. The shotcrete should be designed to carry the load from a loose block, which is assumed to be transferred to the surrounding rock mass over a narrow band. It is commonly accepted that the width of this band is constant, and independent of the shotcrete thickness. In this paper, numerical simulations are used to show that the width of this band and the load capacity is strongly correlated to the mean shotcrete thickness around the perimeter of the block. Furthermore, it is also shown that a strong linear correlation exists between the mean bond strength and the rock support capacity. Based on this, a lower bound function to estimate the structural capacity for the lining is suggested. No correlation was found between the structural capacity and the minimum or maximum shotcrete thickness or bond strength. This indicates that, under certain conditions, local areas with low thickness and bond strength can exist around the block perimeter without having any significant effect on the rock support capacity.